High performance diamond-based solar-blind photodetectors enabled by Schottky barrier modulation. (5th November 2022) - Lin, Chao-Nan; Zhang, Zhen-Feng; Lu, Ying-Jie; Yang, Xun; Zhang, Yuan; Li, Xing; Zang, Jin-Hao; Pang, Xin-Chang; Dong, Lin; Shan, Chong-Xin
Abstract: Diamond, which possesses an ultra-wide bandgap, high thermal conductivity, and super thermal and chemical stability, is a promising material for deep-ultraviolet optoelectronics. However, it is still difficult for diamond photodetectors to meet the requirements of practical applications due to their relatively low responsivity. Here, we demonstrate a high-performance diamond photodetector realized via Schottky barrier modulation. Defect states and hydrogen terminals are introduced onto the surface of the diamond by hydrogen plasma treatment. Under illumination, photon-generated electrons are trapped by the defect states at the surface of the diamond, which lowers dramatically the Schottky barrier height, leading to high photocurrent of the photodetector. As a result, our device exhibits a responsivity of 524.9 A/W, a gain of 2958, and a detectivity of 3.42 × 10 15 cm Hz 1/2 W −1, all of which are among the highest values ever reported for diamond-based photodetectors. Thus, our results suggest a novel strategy for design and fabrication of high-performance diamond photodetectors. Graphical abstract: An MSM-structured diamond photodetector was fabricated with hydrogenated diamond. The photodetector shows a responsivity of as high as 524.9 A/W and a detectivity of 3.42 × 10 15 cm Hz 1/2 W −1 . Image 1 Highlights: An MSM-structured diamond photodetector with high responsivity is realized via a Schottky barrier modulation strategy. Traps are introduced by hydrogen plasma treatment to trap photogenerated electrons, lowering the Schottky barrier heights. The photodetector shows a responsivity of 524.9 A/W, which is among the highest values for diamond photodetectors.